Showing Mercy to the Ungodly and the Inversion of Invective in Jude. (8th March 2018) - Robinson, Alexandra; Llewelyn, Stephen; Wassell, Blake
Abstract : The present paper offers a new interpretation of the three-clause reading of Jude 22–23 and demonstrates how Jude carries on the Jesus tradition by inverting the norms of invective. It is demonstrated that this interpretation is especially surprising given that the epistle follows many conventions of Greco-Roman invective. Given the character of invective, one would expect the writer to instruct the beloved to expel the ungodly from the community. Instead, Jude commands the beloved to 'show mercy' to the very ones with whom they contend (Jude 22), a profound reflection of Jude's understanding of mercy and faith.